Unheimlich: Struktury Pustki w berlińskim muzeum Libeskinda - Kamczycki, Artur (Studia Europaea Gnesnensia, 2014)
The Museum of 2000 years of German-Jewish History in Berlin, designed in 1989 by Daniela Libeskind, an architect of Polish origins, was to make a powerful reference to the Holocaust as well. Using an underground passage, the architect connected the existing Baroque edifice of the Kollegienhaus in Kreuzberg’s Lindenstrasse, with the building created to his design (the so-called Abteilung). The external form of the buildings is a steel, flat-topped structure, composed of cubical blocks, irregular and marked by incisive edges. Inside, this zig-zagging building was intersected by a straight structure, 4.5 m wide, 27 m high and 150 long, which runs interruptedly along the main axis. The resulting empty spaces, extending from the ground floor to the roof, are tightly isolated from the remaining sections of the edifice. The analysis conducted by the author targets the comparison of that structure of the Void with the Freudian notion of the Unheimlich (uncanny). The comparison was made in a conversation with Libeskind by the originator of the theory of deconstruction, Jacques Derrida. Unheimlich is a psychological notion, which in this case denotes “secret”, “hidden” Jewishness, which instead of remaining an “internally closed” aspect is manifested as a characteristic, “negative” reflection. The term, entangled in the context of architectural theory as well as in the notion of anti-monument, represents a starting point in considering the contemporary condition of German culture, where that Void /unheimlich is a constant, “burdensome” echo of the Holocaust.